2019
DOI: 10.3920/bm2018.0074
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum and Lactobacillus plantarum increased gut microbiota diversity and functionality, and mitigated Enterobacteriaceae, in a mouse model

Abstract: Probiotics should bring ‘balance’ to the intestinal microbiota by stimulating beneficial bacteria, whilst mitigating adverse ones. Balance can also be interpreted as high alpha-diversity. Contrary, Escherichia coli is often regarded as an adverse component of the resident intestinal microbiota. The aim of the present study was to implement a mouse model for in vivo screening of Lactobacillus-strains for ability to increase gut-microbiota diversity and to mitigate E. coli. Mice were divided into six groups, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…have been extensively reported in recent years. Apart from their contribution to diversity and functionality of the gut microbiota, it has also been reported that they are associated with improved physiological function and cognitive ability [ 12 , 77 , 78 ]. In addition, the ameliorative impact of Lactobacillus spp.…”
Section: Redox Role Of Lactobacillus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…have been extensively reported in recent years. Apart from their contribution to diversity and functionality of the gut microbiota, it has also been reported that they are associated with improved physiological function and cognitive ability [ 12 , 77 , 78 ]. In addition, the ameliorative impact of Lactobacillus spp.…”
Section: Redox Role Of Lactobacillus Sppmentioning
confidence: 99%
“…regarding the balance they are able to bring to the gut microbiota. For example, supplementations of different combinations of L. fermentum and L. plantarum have been reported to affect diversity and functionality of the gut microbiota in mice [ 12 ]. According to 16S rRNA (ribonucleic acid)-gene compositional data, the combination of two L. fermentum strains (GOS47 and GOS1) may contribute to the enhanced anti-inflammatory activity of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…It is also able to mitigate liver damage and weakened intestinal permeability of the intestines caused by obesity. Additionally, L. plantarum has been reported to increase the diversity of the enteric flora 39,40 , reduce the severity of colitis 41,42 , and it has also demonstrated anti-tumor effects 43 . Lactobacillus rhamnosus has been shown to decrease the amount of colon aberrant crypt foci and reduce pro-carcinogenic biomarkers in a rat model 44 , lower cholesterol 45 , and improve insulin resistance and obesity induced by high-fat diet 46 .…”
Section: Genus Lactobacillus (Lactic Acid Bacteria)mentioning
confidence: 99%
“…A mixture of probiotics showed more efficient eradication of pathogenic Enterobacterales in vivo. In mice, the mixture of L. fermentum GOS47 and L. fermentum GOS1 significantly decreased the viable count of Enterobacterales with potential anti-inflammatory activity and short-chain fatty acid production [ 27 ]. Thus, the favorable effect of probiotic supplements on at least the partial elimination of pathogenic Enterobacterales , ex vivo and in vivo, has promoted their application in clinical diseases.…”
Section: Introductionmentioning
confidence: 99%